Прецизионный компаратор трансформаторов тока - Сурду, М.Н.; Ламеко, А.Л.; Мелещук, Д.В.; Кикало, В.Н.; Копшин, В.В. (Технічна електродинаміка, 2011)
Verification of the current measurement transformers on the power frequency is taken up. The description for operation principles and constructions of precision current comparator are represented. Comparator provides measurement of relative currents difference of high precision. Measurement chain of device is equilibrated with help of inductive divider. Calculation of the result of measurement is operated with taking of final non-equilibrium signal that permits us to receive high precision of measurements during lessening of inductive divider. The device is elaborated for determination of current transformers error by method of standard transformer comparison. There is also measurement of relative voltage difference in the device. It helps in determination of windings errors of transformers by comparison with a reference winding located on the test transformer.